Beta-blockers in the treatment of heart failure CIBIS III Trial - Banach, Maciej; Barylski, Marcin (Przewodnik Lekarza/Guide for GPs, 2005)
Heart failure is a very important problem in health care system. In Europe there are almost 10 millions and in Poland half a million patients with left ventricular dysfunction. Heart failure is a clinical disorder characterized by insufficient perfusion of peripheral tissues and fluid retention. Improvement of heart contractility is one of the major therapeutic aims among patients with left ventricular dysfunction. The exact knowledge of methods of heart assistance is indispensable in practice both cardiologist, cardiac surgeons and general practitioners. Beta-blockers are the most important medicines used in the treatment of heart failure. Each new clinical trial informs about the additional benefits resulting of their application. The similarly effect we have already observed during recent presentation of CIBIS III.